African Countries' Debt: A Tale of Acceleration at Multiple Speeds and Shades. (8th November 2021) - Songwe, Vera; Awiti, Christine
Abstract: Over 50% of African countries had debt to GDP ratios above 50% in 2019 with at least 48% of countries having debt to GDP ratios above 70%. The rise in debt levels is a recent phenomenon, with most countries' debt increasing between 2014 and 2019. In this paper, we propose a new approach to debt monitoring. We argue that the speed of debt accumulation matters and that monitoring the speed of debt could alter the path of debt to more sustainable debt levels. We carry out an empirical analysis for all African countries in the 10 years to 2018 and group countries into seven categories based on their speed of growth of debt and their debt levels. We find that there is heterogeneity in country debt acquisition and that ensuing policies to ensure sustainable debt will need to be country specific.